Advantages of using monolithic silica gel columns in the pharma industry: biomolecule separation - Machtejevas, Egidijus (Henry Stewart Talks, 2021)
HPLC analysis, Monolithic columns, Pore structure of monolithic columns, Advantages and applications of monolithic columns, Monolithic column modifications, Immobilization, The Schiff base method, Bioreactors